Polyunsaturated fatty acid type and ratio in lipid supplements alter the in vitro dry matter digestibility of kikuyu grass (Cenchrus clandestinus) (2017)
ABSTRACT: Two experiments were conducted to investigate the effects of polyunsaturated fatty acid (PUFA) type and ratio in lipid supplements on the in vitro dry matter digestibility (IVDMD) of kikuyu grass. For this purpose, kikuyu grass (Cenchrus clandestinus) was incubated into rumen inoculum with a) 18 μL of linoleic (LA) and alpha-linolenic (LN) acid mixtures (LA:LN = 100:0, 75:25, 50:50, 25:75 or 0:100) (Experiment 1), or b) 18 μL of docosahexaenoic (DHA) and eicosapentaenoic (EPA) acid mixtures (DHA:EPA = 100:0, 75:25, 25:75, and 0:100) containing a constant LA:LN 75:25 ratio (experiment 2). Differences between treatments were analyzed as a completely randomized design using the MIXED procedure of SAS. Also, for experiment 1, IVDMD was regressed to the ratio between LA and LN concentrations (LA/LN) in the incubation systems at 0 h of digestion, using the REG procedure of SAS. In experiment 1, the supplementation with LA pure and mixed with LN in LA:LN= 75:25, 50:50, and 25:75 ratios, decreased by 3.4% the IVDMD of kikuyu grass, whereas the supplementation with LN pure, increased by 3.1% the IVDMD (P < 0.01). Also, a polynomial model was built to predict the IVDMD from the LA/LN ratio into incubation systems (P < 0.01): IVDMD = - 0.118 × (LA/LN)3 + 1.45 × (LA/LN) 2 – 4.81 × (LA/LN) + 69.7. In experiment 2, the supplementation with a 75:75 LA:LN mixture combined or not with 100:0, 75:25, and 25:75 DHA:EPA mixtures, decreased by 4.2% the IVDMD of kikuyu grass, while the supplementation with EPA pure decreased by 2.3% the IVDMD(P < 0.01). These results suggest that LA and DHA may be more detrimental than LN and EPA during the ruminal dry matter digestibility of kikuyu grass. Also, our study indicated that the IVDMD of kikuyu grass can be predicted, from the ratio between LA and LN concentrations in the incubation systems at 0 h of digestion. This information may be used for optimizing the design of lipid supplements in ruminant nutrition.